(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article touches upon the current problems of the discipline «Russian language» for foreign students in the conditions of a research university. The alternatives for solving the problems in the educational process, which took place in the conditions of a research university, are offered. According to the authors’ recommendations, «Russian language» for foreign students should be conducted as a separate discipline «Russian as a foreign language». Based on this, the authors propose the thematic content of the electronic manual. A scientific review of textbooks and teaching aids within the discipline «Russian language» has been conducted. As a result, it is found that their content corresponds to the ideas provided in the tasks of the research university. Also reflected are the results of the questionnaire survey conducted to identify difficulties in the learning process of foreign students and to determine the need to teach Russian as a foreign language. The purpose of the article is to determine the correspondence of the content of the discipline of the Russian language in real conditions to the goals and objectives of the research university and, on this basis, to present a model of a new electronic textbook. As a result of the study, the authors determine the necessity of a textbook (electronic) for foreign students and emphasize the importance of its compliance with the goals and objectives of a research university. In the case of solving the actual problem raised in the article, the results can be used to update the content of the discipline «Russian language» in the university. Keywords: Russian as a foreign language, textbook, research university, educational process, Al-Farabi KazNU.